Low autophagy capacity implicated in motor system vulnerability to mutant superoxide dismutase - Tokuda, Eiichi; Brännström, Thomas; Andersen, Peter M.; Marklund, Stefan L. (Acta neuropathologica communications, 2016)
The motor system is selectively vulnerable to mutations in the ubiquitously expressed aggregation-prone enzyme superoxide dismutase-1 (SOD1). Autophagy clears aggregates, and factors involved in the process were analyzed in multiple areas of the CNS from human control subjects (n = 10) and amyotrophic lateral sclerosis (ALS) patients (n = 18) with or without SOD1 mutations. In control subjects, the key regulatory protein Beclin 1 and downstream factors were remarkably scarce in spinal motor areas. In ALS patients, there was evidence of moderate autophagy activation and also dysregulation. These changes were largest in SOD1 mutation carriers. To explore consequences of low autophagy capacity, effects of a heterozygous deletion of Beclin 1 were examined in ALS mouse models expressing mutant SOD1s. This caused earlier SOD1 aggregation, onset of symptoms, motor neuron loss, and a markedly shortened survival. In contrast, the levels of soluble misfolded SOD1 species were reduced. The findings suggest that an inherent low autophagy capacity might cause the vulnerability of the motor system, and that SOD1 aggregation plays a crucial role in the pathogenesis.